1998
DOI: 10.1046/j.1365-2362.1998.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recombinant human growth hormone treatment on psychological profiles in hypopituitary patients with adult‐onset growth hormone deficiency

Abstract: The data demonstrate that low rh-GH dosages significantly improve psychological profiles as rated by HDS evaluation in adult-onset patients with GHD. On the other hand, a 6-month period of treatment does not produce any significant differences in quality of life as measured by KSQ between treated patients and placebo controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
3
21
1
Order By: Relevance
“…Specifically, because it relates to the findings of GHD and hypogonadism in this study, GH replacement is known to improve QoL in patients with adult-onset GHD and helps reduce fat mass and improve exercise capacity. 51,52,54,55,[74][75][76][77][78][79][80] The benefits of testosterone therapy for men are clear and considered standard practice. 50,57,81 In addition, the high prevalence of MetS in retired football players is important because lifestyle changes may reverse some of these findings and improve the cardiovascular and metabolic disease risks that are associated with MetS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, because it relates to the findings of GHD and hypogonadism in this study, GH replacement is known to improve QoL in patients with adult-onset GHD and helps reduce fat mass and improve exercise capacity. 51,52,54,55,[74][75][76][77][78][79][80] The benefits of testosterone therapy for men are clear and considered standard practice. 50,57,81 In addition, the high prevalence of MetS in retired football players is important because lifestyle changes may reverse some of these findings and improve the cardiovascular and metabolic disease risks that are associated with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Both GHD and hypogonadism have been associated with poor QoL. [49][50][51][52][53][54][55][56][57][58][59][60] In addition to poor QoL, both GHD and hypogonadism can contribute to decreased lean body mass, increased fat mass (in particular, visceral fat), and poor exercise capacity that further contribute to poor QoL, obesity, and MetS, increasing cardiovascular disease (CVD) risk. 51,54,57,[61][62][63][64][65][66][67][68][69][70] Studies have shown that MetS is associated with, and predicts the development of, low serum testosterone levels in men.…”
Section: Previous Studies On Postconcussive Hypopituitarismmentioning
confidence: 99%
“…Three trials included participants with adult onset GH deficiency only (Bengtsson et al 1993, Baum et al 1998, Giusti et al 1998, one had participants with child onset GH deficiency only (Deijen et al 1996) while the remainder included both child and adult onset participants. In all trials that reported data, participants with multiple and isolated deficiencies were included.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…Only five trials (29·5%) reported both withdrawals from the study because of adverse events and specific adverse events with numbers per study arm and per type (Whitehead et al 1992, Beshyah et al 1995, Verhelst et al 1997, Baum et al 1998, Cuneo et al 1998. Six further trials (35%) reported either withdrawal details (Bengtsson et al 1993, Florkowski et al 1998, Giusti et al 1998, de Novaes Soares et al 1999 or specific adverse event details (Attanasio et al 1997) or partial data on specific adverse events (Wallymahmed et al 1997). Six trials (35%), however, did not report information on either withdrawals or specific adverse events (McGauley 1989, Degerblad et al 1990, Burman et al 1995, McKenna et al 1997a,b, Deijen et al 1996.…”
Section: Adverse Event Reportingmentioning
confidence: 99%
See 1 more Smart Citation